Morphological characteristic of the white rats pituitary gland at the different stages of postnatal ontogenesis. - Bobrysheva, I. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Currently, much attention is paid to the study of pituitary organometry in age aspect, however, peculiarities of ultramicroscopic structure of adenohypophyseal endocrine cells of the laboratory animals that are most commonly used in experimental studies are not fully investigated. Objective. To study the features of ultramicroscopic structure of endocrine cells of the distal part of pituitary gland of white rats at the different stages of postnatal ontogenesis. Methods. 18 intact white male rats were subdivided into three groups according to their age: puberty (with mass of 30-50 g), reproductive (130-150 g) and period of the expressed senile changes (300-330 g). Ultrathin sections were investigated with the help of electron microscopy. Following indexes of the endocrine cells of pituitary gland were determined: cross section area of nucleoli in a nucleus; cross section area of mitochondria; cross section area of secretory granules of cytoplasm, among the last area of active granules was calculated separately. Results. The presence of features of the ultrastructure and morphometric parameters of endocrine cells in the anterior pituitary of animals of different age groups was shown. The pituitary gland of intact rats of reproductive period contained endocrine cells in which the system of protein synthesis organelles was formed. The changes found in the animals of reproductive period reflect the increase of functional activity in all types of endocrine cells. In the rats of period of the expressed senile change decrease of secretory activity of endocrine cells of pituitary gland was demonstrated. Conclusion. Differences in the activity of adenohypophyseal endocrine cells depending on life period of investigated animals was revealed.